2004
DOI: 10.1002/ajim.20043
|View full text |Cite
|
Sign up to set email alerts
|

Lack of modulating influence of GSTM1 and GSTT1 polymorphisms on urinary biomonitoring markers in coke‐oven workers

Abstract: GST may not play a role in the regulation of metabolism of urinary biological markers in COWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…In the present study, it was found that this GSTM1 polymorphism was not associated with the levels of DNA damage in the coke-oven workers. Meanwhile, the absence of an association between the GSTT1 variant genotype and the Olive TM values was also consistent with reports from many other studies (24,39,40). Therefore, it is likely that the polymorphisms of GSTM1 and GSTT1 have no effect at all on DNA damage levels, at least in peripheral blood lymphocytes, among subjects exposed to PAHs.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, it was found that this GSTM1 polymorphism was not associated with the levels of DNA damage in the coke-oven workers. Meanwhile, the absence of an association between the GSTT1 variant genotype and the Olive TM values was also consistent with reports from many other studies (24,39,40). Therefore, it is likely that the polymorphisms of GSTM1 and GSTT1 have no effect at all on DNA damage levels, at least in peripheral blood lymphocytes, among subjects exposed to PAHs.…”
Section: Discussionsupporting
confidence: 90%
“…Yang et al (2003) found higher 1-OHP levels in GST1+ genotypes than the GSTT1-genotypes in smokers whereas other workers (Hong et al, 1999;Alexandrie et al, 2000;Nan et al, 2001;Wu et al, 2004b) could not find this in coke oven workers or smokers. It is known that 1-OHP is mainly excreted as the glucuronide conjugate.…”
Section: Discussionmentioning
confidence: 83%
“…Although several lines of evidence showed that variant genotypes of cytochrome P450 such as CYP1A1 and CYP2E1 could modify the metabolism of PAH in coke-oven workers (24)(25)(26), other studies reported no correlations between cytochrome P450 polymorphism and urinary 1-OHP level (9,(27)(28)(29). Therefore, it is hard to interpret the relation between cytochrome P450 polymorphism and urinary 1-OHP level.…”
Section: Discussionmentioning
confidence: 99%